Emotion and Altruism: The Psychological Foundations of Community Mental Health Responses - Widyanti, Eka (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
This narrative review investigates the intersection of psychological, emotional, and contextual determinants in prosocial behavior and moral decision-making within mental health frameworks. The study aims to synthesize current empirical and comparative findings on how variables such as empathy, guilt, social norms, and cultural settings shape individual responses in social contexts. The review employed a rigorous literature search across four major academic databases—PubMed, Scopus, Web of Science, and Google Scholar—using Boolean combinations of keywords including "mental health," "community-based intervention," "psychosocial support," and "prosocial behavior." Inclusion criteria centered on peer-reviewed studies involving experimental and cross-cultural methodologies within the past decade. Findings indicate that emotions such as guilt and empathy significantly impact moral choices and prosocial tendencies, especially within environments characterized by collective norms and community support. Cultural comparisons reveal that collectivist societies exhibit stronger emotional responses and higher propensities for altruistic behavior. Moreover, contextual elements like group pressure, power dynamics, and access to supportive structures further modulate behavioral outcomes. Despite these insights, systemic barriers such as policy fragmentation and societal stigma remain significant impediments. The study underscores the importance of integrating emotional intelligence, social norm transformation, and structural support into mental health strategies. It recommends community-engaged interventions, digital advocacy, and cross-sector partnerships to promote sustainable solutions. These findings offer actionable implications for policy reform and future empirical research aimed at enhancing prosocial engagement globally.